A Randomized Trial Testing the Impact of Narrative Vignettes vs. Guideline Summaries on Provider Response to a Professional Organization Clinical Policy for Safe Opioid Prescribing - Meisel, Zachary F. (Ann Emerg Med, 2016)
BACKGROUND: Clinical guidelines are known to be underused by practitioners. In response to the challenges of treating pain amidst a prescription opioid epidemic, the American College of Emergency Physicians published an evidence-based clinical policy for opioid prescribing in 2012. Evidence-based narratives, an effective method of communicating health information in a variety of settings, offer a novel strategy for disseminating guidelines to physicians and engaging providers with clinical evidence. OBJECTIVES: To compare whether narrative vignettes embedded in the American College of Emergency Physician (ACEP) daily e-newsletter improved dissemination of the clinical policy to ACEP members, and engagement of members with the clinical policy, compared to traditional summary text. METHODS: A prospective randomized controlled study, entitled Stories to Promote Information using Narrative (SPIN) trial, was performed. Derived from qualitative interviews with 61 ACEP physicians, 4 narrative vignettes were selected and refined, using a consensus panel of clinical and implementation experts. All ACEP members were then block randomized by state of residence to receive alternative versions of a daily emailed newsletter for a total of 24 days during a 9 week period. Narrative newsletters contained a selection of vignettes that referenced opioid prescription dilemmas. Control newsletters contained a selection of descriptive text about the clinical policy using similar length and appearance to the narrative vignettes. Embedded in the newsletters were web links to the complete vignette or traditional summary text, as well as additional links to the full ACEP clinical policy and a website providing assistance with prescription drug monitoring program enrollment. The newsletters were otherwise identical. Outcomes measured were the percentage of subjects who visited any of the web pages that contained additional guideline related information and the odds of any unique physician visiting these web pages during the study. RESULTS: 27,592 physicians were randomized and 21,226 received the newsletter during the study period. When counting each physician once over the study period, there were 509 unique visitors in the narrative group and 173 unique visitors in the control group (4.8% vs. 1.6%, difference 3.2% 95%CI 2.7%-3.7%). There were 744 gross visits from the e-newsletter to any of the three web pages in the narrative group compared to 248 in the control group (7.0% vs. 2.3%, OR 3.2 (95% CI 2.7-3.6). Over the course of the study, the odds ratio of any physician in the narrative group visiting one of the three informational web sites compared to the control group was 3.1 (95% CI 2.6-3.6). CONCLUSION: Among a national sample of emergency physicians, narrative vignettes outperformed traditional guideline text in promoting engagement with an evidence-based clinical guideline related to opioid prescriptions.